On the trails of environmental education: for a renewed relationship with mangrove ecosystems - ANDRADE, João Angelo Peixoto de; MATOS, Fábio de Oliveira (Geosaberes; Vol 7 No 12 (2016): Jan - JuneDO - 10.26895/geosaberes.v7i12.525, 2016)
The environmental problems result from a synergy originated in the inconformity of the multiple socioenvironmental interactions compounding the global environment because of human activities. This work transits through varied knowledge linked to the environmental dimension, relating them to the importance of natural systems conservation on maintaining the global environmental quality, boarding mangroves as an example, and the mangrove ecosystem in the Environmental Protection Area (EPA) of the Ceará River Estuary as a case study. The EPA, located on the boundaries of the cities of Fortaleza and Caucaia/CE, houses a mangrove ecosystem under strong pressure resulting from human activities; Mangroves respond for several environmental functions and services; fact, per se, justifiable for environmental protection. So, it is suggested the Environmental Education (EE) in order to trail the multiple environmental dimensions in its interactions; acknowledging its mediator and uniting finality concerning varied knowledge in the scope of socio-environmental justice.
Keywords: APA do Rio Ceará, Manguezal, Educação Ambiental.